Synthesis, structural characterization and Mössbauer study of LnV 0.5Fe 0.5O 3 perovskites (Ln = Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho and Er) - Ivashita, Flávio F. (2012)
Perovskites LnV 0.5Fe 0.5O 3 (Ln = Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho and Er) were synthesized by rapid solidification from arc-melted samples and characterized by the study of their crystal structure and hyperfine properties. These metastable solid solutions crystallized in the Pbnm symmetry, with the iron and vanadium cations randomly distributed in the transition metal octahedral sites. Depending on the lanthanide present at the A site of the perovskite, iron is present with two valences (i.e., Fe 3+ and Fe 2+). The volume of the unit cell for these perovskites increases linearly with the lanthanide ionic radius, as the perovskite approaches its ideal structure. At room temperature, the quadrupolar splitting of the trivalent paramagnetic Mössbauer component works as an indirect measurement for the Goldshmidt tolerance factor. Close to or below 100 K, these perovskites undergo a crystallographic phase transformation, probably due to orbital ordering of the V 3+ cations, originating two different magnetic iron sites. © 2012 Elsevier Ltd.